FACTORS ASSOCIATED WITH HAND WASHING WITH SOAP (CTPS) BEHAVIOR AMONG STUDENTS AT SMPN 3 KOTA SABANG - Zuriati, Nura; Santi, Tahara Dilla; Maidar, Maidar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Optimal levels of public health can be achieved through various efforts, one of which is disease prevention through hand washing with soap (CTPS). School-age children are prone to various diseases due to low CTPS behavior. The aim of the study was to determine the factors related to CTPS among students at SMPN 3 Kota Sabang. Methods: The research method uses descriptive analytics with a cross- sectional approach. This research was conducted at SMPN 3 Kota Sabang with a sample of 85 students in class VII and VIII. Data collection uses a structured questionnaire instrument. Data analysis uses univariate analysis to display the frequency distribution of each variable and bivariate analysis uses the chi-square test. Result: The results show that there is a relationship between knowledge (p value = 0.001), attitude (p value = 0.002), and the role of health workers (p value = 0.000) with CTPS behavior, and there is no relationship between the teacher's role (p value = 0.462) with CTPS behavior. Recommendation: It is hoped that School Health Unit (UKS) officers can provide more extensive education to students about the benefits of CTPS.